Experimental Study of the Angle of Repose of Coral Sands - Zhen Yao; Jie Chen; Changbo Jiang; Zhiyuan Wu; Bin Deng; Yuannan Long; Hongtao Zou; Jinwei Zhang; Runze Bai (Journal of Marine Science and Engineering, 2025)
The angle of repose is a fundamental parameter for assessing the stability of coral reefs. However, predictive models for this angle are currently lacking. In this study, a series of laboratory experiments were undertaken to investigate the angle of repose by varying moisture content, particle shape, and particle size. Based on our experimental data, variation in the angle of repose with moisture content is classified into five distinct zones. It is demonstrated that the range of moisture content for each zone varies with particle size. Coral sands of dendrite, flake, rod, and block particles have a descending order of angle of repose, as demonstrated for a sieve size of 4.5 mm. The angle of repose for dry, submerged, and steady coral sands exhibits a correlation with the nominal diameter of particle size. Finally, extended models are proposed for predicting the angle of repose of coral sands (R2 = 0.8, Dn50 = 0.317−5.470). To facilitate use of these models, a linear relationship between sieve particle size diameter, nominal particle size diameter, and Corey shape factor, allowing for conversion among these parameters, is established. This study thereby helps to enhance our understanding of how moisture content affects angle of repose and improve our ability to predict the angle for coral grains with intricate geometries.